Pembaruan Pendidikan Islam K.H. Hasyim Asy’ari - As'ad, Mahrus (Universitas Darussalam Gontor, 2012)
The characteristic of the Indonesia Islamic education modernism is largerly determined by the creativity which the Muslim pointed out. The flexibility of the Islamic education system enable it to easily adapt itself to the surrounding and to create the new and appropriate format of its derivation in line with the new demand of the umma for the field in the modern era. A number of experiments had been performed by the Muslim figures, individually or collectively , to fulfill that demand in the early decades of the 20th century. How did they adopt the elements of modernity to keep the Islamic education remain in its own identity? For this purpose, it is important to understand and to explain the ideas and the efforts of Syaikh Hasyim Asy’ari of Tebuireng in modernizing his pesantren and its main contribution to the development of the new madrasahs in the country. Using the analytical-critical method, this examination is in conclusion that Hasyim’s allegiance to stand on his traditional bases in modernizing his pesantren has created a something useful for directing the orientation and giving the strong foundation of the Indonesia’s Islamic education modernism. His success in harmonizing the elements of modernity with the Islamic traditions under the religious inspection as the pivotal axis is his real contribution to the new madrasah with its own identity to distinct itself with the public school, though the government has “nationalized” the first to be in equivalent to the public school.